2008
DOI: 10.1063/1.3006085
|View full text |Cite
|
Sign up to set email alerts
|

Torus-shaped dust clouds trapped in a magnetized anodic plasma

Abstract: Dust particles confined in a magnetized anodic plasma can form a torus-shaped cloud with a dust-free region (void) in the center. Most of the dust particles perform a rotational motion about the major axis of the torus. The torus-shaped dust cloud and the velocity of the particles are studied by varying the external plasma parameters like magnetic field strength and rf-power of the source plasma. Two-dimensional potential contours are measured with an emissive probe. The results are used to discuss the force b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…When the grains have larger displacements, or if particle tracking fails due to other considerations (such as high dust number density), particle image velocimetry (PIV) has been shown to be an effective method to measure the average velocity vector for small groups of particles within a dust cloud. [6][7][8][9][10] The dust component of the plasma observed within the experiment described in this study was found to be weakly coupled (fluid-like) with number densities on the order of 10 10 m À3 , making PIV the applicable image analysis technique for the system.…”
Section: Introductionmentioning
confidence: 97%
“…When the grains have larger displacements, or if particle tracking fails due to other considerations (such as high dust number density), particle image velocimetry (PIV) has been shown to be an effective method to measure the average velocity vector for small groups of particles within a dust cloud. [6][7][8][9][10] The dust component of the plasma observed within the experiment described in this study was found to be weakly coupled (fluid-like) with number densities on the order of 10 10 m À3 , making PIV the applicable image analysis technique for the system.…”
Section: Introductionmentioning
confidence: 97%
“…In some of these experiments, magnetic field was applied. [7][8][9][10][11][12][13] In presence of magnetic field, the electric field inside the plasma induces an azimuthal (E Â B) rotation of ions. It causes the levitated dust particles to rotate in azimuthal direction at low pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a new experiment by Pilch, et al has shown the formation of torus-shaped particle clouds produced by ion E × B flows in the anode spot of a glow discharge plasma with increasing magnetic field strength [136]. These studies illustrate that the presence of a magnetic field -even without a direct effect on the charged dust -can play a significant role in modifying the properties of dusty plasmas.…”
Section: Magnetic Field Effectsmentioning
confidence: 96%